Optimization of a novel dental self-healing resin composite by bacteria-induced biomineralization - Han, Yanyan; Zhang, Xiaoxuan; Weng, Jianing; Tian, Shiqi; Dong, Xian; Cai, Zhiheng; Zhang, Yi; Wu, Tiantian; Lin, Dan; Zhu, Yaqin (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDental resin restorations often fail due to microcrack expansion, causing fractures and secondary caries. Self-healing resin composites based on Microbially Induced Calcium Carbonate Precipitation (MICP) offer a solution. In these composites, moisture and air activate bacteria to precipitate calcium carbonate (CaCO3) and repair microcracks. When a crack seals, bacteria become dormant or form spores until the next crack forms, triggering repeated self-healing.MethodsThis study involved the optimization of nutrients to enhance biocompatibility, the preparation of dental resin composites incorporating eight different bacterial strains, the investigation of Mn2+ to enhance self-healing properties, and the utilization of a method to evaluate self-healing efficiency tailored for the oral environment. This method took a microscopic view of the healing process in artificial saliva, and the self-healing efficiency was determined by quantifying the scratch area.ResultsIn the final results, Bacillus sphaericus (ATCC 4525) cultured with Mn2+ exhibited the most impressive self-healing effect, while Bacillus pasteurii (B80469) had the weakest self-healing effect in the study. Otherwise, Bifidobacterium longum showed no significant difference between its initial and secondary healing effects.DiscussionThis dental self-healing resin composite can undergo multiple rounds of self-repair and boasts high biocompatibility, leading to a significant reduction in the failure rate of dental resin restorations.